IMPROVING THE EFFICIENCY OF FOREIGN ECONOMIC ACTIVITY OF ENTERPRISES ON THE BASIS OF MARKET RESEARCH - Gontareva, Iryna; Nesen, Mariia (Соціальна економіка, 2023)
The article is aimed at studying the status and trends in the development of foreign economic activity in Ukraine and in the world, and the impact of marketing research on their efficiency. The purpose of the study is to analyze the improvement of the efficiency of foreign economic activity of enterprises on the basis of marketing research using economic and statistical methods, to identify problems and prospects for development, and to develop ways for effective foreign economic activity in conducting marketing research. The article provides data on the volume of the marketing data market worldwide as of 2017-2021, the results of a survey of European companies on the benefits received after investing in sustainable marketing strategies as of July 2022. To achieve the goal, the following tasks were set and solved: identifying the characteristic features of the organization's activities, familiarizing with the principles of accounting and financial reporting, analyzing the marketing and foreign economic activities of organizations. The importance of the development of foreign economic activity and market relations due to increased responsibility and independence of industries and individual entities in the preparation and adoption of management decisions is determined. The relevance of studying the theoretical aspects of improving the efficiency of foreign economic activity of enterprises based on the impact of marketing research on the functioning of these processes is substantiated. The impact of investing in sustainable marketing strategies on the company's development is characterized. The main obstacles to entering a new market are indicated. The results are summarized and ways to improve the functioning of foreign economic activity in Ukraine in the course of marketing research in the company are proposed, through the implementation of certain measures. It is determined that the main areas for further research should be: identifying the most attractive marketing strategies in international markets, how artificial intelligence can become a driving mechanism in the company's marketing, studying pricing strategies and developing financial marketing mechanisms in accordance with this data, the impact of e-commerce in international operations and the proper management of these strategies.